Unidirectional Lightweight Encapsulation With Header Compression For IP Based Satellite Communication Over DVB-S. - Wan, Tat-Chee (2007)
The Multi-Protocol Encapsulation (MPE) is a standard method for encapsulating IP packets into MpEG-2 TS frames. However MPE has some disadvantages in simplicity and efficiency to support next generation network.